2015
DOI: 10.4314/ahs.v14i4.19
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and heart rate adjustment following acute Frenkel’s ambulatory exercise in chronic hemiparetics stroke survivors: a comparative study

Abstract: Background:Frenkel's ambulatory activity has been routinely employed by physiotherapists for rehabilitation of gait coordination, however, its immediate influence on blood pressure and heart rate has not been investigated. Objective To investigate the acute effect of Frenkel's ambulatory activity on blood pressure and heart rate of chronic hemiparetic stroke survivors. Method Using a comparative study design, 60 chronic hemiparetic stroke survivors of varying onset of stroke, ≤6, >6-11 and ≥12 months were subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the subject literature, there are not any published results of studies assessing the SBP value during SMWT and SCT. Data from the available literature have shown an increase in SBP value during and after the completion of exercise stress test [ 36 ] as well as during exercise in patients after IS [ 37 ]. In our studies, in the post-stroke group, signs of myocardial ischemia were observed in the ECG performed after SMWT and SCT, which were not present in resting ECG.…”
Section: Discussionmentioning
confidence: 99%
“…In the subject literature, there are not any published results of studies assessing the SBP value during SMWT and SCT. Data from the available literature have shown an increase in SBP value during and after the completion of exercise stress test [ 36 ] as well as during exercise in patients after IS [ 37 ]. In our studies, in the post-stroke group, signs of myocardial ischemia were observed in the ECG performed after SMWT and SCT, which were not present in resting ECG.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic stroke patients seem to need careful monitoring of their blood pressure before, during and after exercise. 20 Keeping with NCDs, serum HE4 seems to be an important marker of benign gynaecological disorders according to Chinese workers. 21 MPV again!…”
mentioning
confidence: 99%